De novo Transcriptome Assembly of the Clown Anemonefish (Amphiprion percula): A New Resource to Study the Evolution of Fish Color - Maytin, Alexander K.; Davies, Sarah W.; Smith, Gabriella E.; Mullen, Sean P.; Buston, Peter M. (Frontiers in Marine Science, 2018)
A fundamental question of evolutionary biology is, why are some animals conspicuously colored? This question may be addressed from both a proximate (genetic and ontogenetic) and ultimate (adaptive value and evolutionary origins) perspective, and integrating these perspectives can provide further insights. Over the last few decades we have made great advances in understanding the causes of conspicuous coloration in terrestrial systems, e.g., birds and butterflies, but we still know relatively little about the causes of conspicuous, ‘poster’ coloration in coral reef fishes. Of all coral reef fishes, the clownfish Amphiprion percula, is perhaps the most conspicuously colored, possessing a bright orange body with three iridescent white bars bordered with pitch black. Here, we review what is known about the proximate and ultimate causes of the conspicuous coloration of clownfishes Amphiprion sp.: coloration has a heritable genetic basis; coloration is influenced by development and environment; coloration has multiple plausible signaling functions; there is a phylogenetic component to coloration. Subsequently, to provide new insights into the genetic mechanisms and potential functions of A. percula coloration we i) generate the first de novo transcriptome for this species, ii) conduct differential gene expression analyses across different colored epidermal tissues, and iii) conduct gene ontology (GO) enrichment analyses to characterize function of these differentially expressed genes. BUSCO indicated that transcriptome assembly was successful and many genes were found to be differentially expressed between epidermal tissues of different colors. In orange tissue, relative to white and black, many GO terms associated with muscle were over-represented. In white tissue, relative to orange and black tissue, there were very few over- or under-represented GO terms. In black tissue, relative to orange and white, many GO terms related to immune function were over-represented, supporting the hypothesis that black (melanin) coloration may serve a protective function. Overall, this study presents the assembly of the A. percula transcriptome, and represents a first step in an integrative investigation of the proximate and ultimate causes of conspicuous coloration of this iconic coral reef fish.